2019
DOI: 10.21203/rs.2.14404/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnitude of Uncontrolled Hypertension and Associated Factors among Adult Hypertensive Patients in Public Hospitals of Central Zone, Tigray, Ethiopia: A Cross-sectional Study 2018

Abstract: Background: - Uncontrolled hypertension is if SBP is ≥140 mm Hg and/or DBP ≥90 mm Hg for general hypertensive population or if SBP ≥130 mm Hg and/or DBP ≥80 mm Hg in patients with established diabetes mellitus or chronic kidney disease based on the average of two or more properly measured, seated, BP readings on each of two or more office visits. The aim of this study was to assess the magnitude of uncontrolled hypertension and associated factors among adult hypertensive patients in public hospitals of central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The odds of non-adherence to antihypertensive medication in those cases were 2 times higher than their counterparts. This study was in line with a cross-sectional study done in different regional areas of study including Ethiopia (Amhara, Tigray) and Brazil (5,15,27,30,44,45). This might be due hypertension treatment requires taking the right drug with the right dose at the right time.…”
Section: Determinants Of Uncontrolled Blood Pressuresupporting
confidence: 81%
“…The odds of non-adherence to antihypertensive medication in those cases were 2 times higher than their counterparts. This study was in line with a cross-sectional study done in different regional areas of study including Ethiopia (Amhara, Tigray) and Brazil (5,15,27,30,44,45). This might be due hypertension treatment requires taking the right drug with the right dose at the right time.…”
Section: Determinants Of Uncontrolled Blood Pressuresupporting
confidence: 81%
“…The twenty-four studies [ 1 , 3 , 6 , 7 , 9 , 11 , 12 , 14 , 18 , 21 – 26 , 28 , 29 , 31 , 38 43 ] and two studies [ 10 , 44 ] were conducted using cross-sectional and retrospective cohort study designs respectively. Regarding geographical region, nineteen studies were found in Ethiopia [ 1 , 3 , 6 , 9 , 10 , 14 , 18 , 21 , 22 , 24 , 26 , 28 , 38 44 ], one study in Kenya [ 23 ], Nigeria [ 7 ], Cameroon [ 12 ], Sudan [ 25 ], South Africa [ 31 ], Tanzania [ 11 ], and selected SSA countries [ 29 ]. The total sample size of the included studies was 11,600, where the smallest sample size was 131 in Ethiopia (Jimma University Medical Center) and the largest sample size was 2,198 in selected SSA countries.…”
Section: Resultsmentioning
confidence: 99%
“…The total sample size of the included studies was 11,600, where the smallest sample size was 131 in Ethiopia (Jimma University Medical Center) and the largest sample size was 2,198 in selected SSA countries. The overall pooled prevalence of uncontrolled hypertension was obtained from all twenty-six included primary studies [ 1 , 3 , 6 , 7 , 9 – 12 , 14 , 18 , 21 – 26 , 28 , 29 , 31 , 38 44 ], while the data regarding the predictors of uncontrolled hypertension were obtained from the twenty-three studies [ 1 , 3 , 6 , 9 – 12 , 14 , 18 , 22 , 24 26 , 28 , 29 , 31 , 38 44 ] with a response rate ranging from 75.72 to 100% ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation